2020
DOI: 10.3390/agronomy10070928
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Energy Crops: Sida hermaphrodita (L.) Rusby and Silphium perfoliatum L.—State of Knowledge

Abstract: Current global temperature increases resulting from human activity threaten many ecosystems and societies, and have led to international and national policy commitments that aim to reduce greenhouse gas emissions. Bioenergy crops provide one means of reducing greenhouse gas emissions from energy production and two novel crops that could be used for this purpose are Sida hermaphrodita (L.) Rusby and Silphium perfoliatum L. This research examined the existing scientific literature available on both crops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 167 publications
(463 reference statements)
3
64
0
Order By: Relevance
“…Under suboptimal conditions of water and phosphorous shortage a higher yield stability of the crop mixtures was demonstrated, which makes them a suitable agronomic alternative to sole cropped maize or sorghum. Similar positive results for intercropping the perennial energy crop S. hermaphrodita with perennial legume species was also demonstrated in earlier studies, and was highlighted in the review-article on this crop by Cumplido-Marin et al [3].…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Under suboptimal conditions of water and phosphorous shortage a higher yield stability of the crop mixtures was demonstrated, which makes them a suitable agronomic alternative to sole cropped maize or sorghum. Similar positive results for intercropping the perennial energy crop S. hermaphrodita with perennial legume species was also demonstrated in earlier studies, and was highlighted in the review-article on this crop by Cumplido-Marin et al [3].…”
supporting
confidence: 85%
“…Both studies clearly identified beneficial effects of the biogenic residues on plant performance in the given experimental time in maize. Such positive effects of digestate application in sand and other soils were also described in earlier greenhouse and outdoor studies using the perennial plant S. hermaphrodita as a promising bioenergy carrier, as described and summarized in the review-article by Cumplido-Marin et al [3]. Overall, in terms of declining mineral phosphorus resources and to reduce the high energy demand for nitrogen and mineral fertilizers in general, nutrient recycling becomes an important issue particularly for bio-energy crop production.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…In recent years, the majority of research on cup plant has focused on its potential as a substitute for maize in biogas production in Europe, especially Germany [197][198][199]. While maize is somewhat higher yielding than cup plant, diversification of bioenergy feedstocks in agricultural landscapes is generally desirable and cup plant is perceived as providing more ecosystem services than maize [198].…”
Section: Dual-use Oilseedsmentioning
confidence: 99%
“…As a result of the conducted study, it was determined that cup plant dry weight yield increased with the increase in the level of fertilization and irrigation ( Figure 2). Other cultivation studies have shown that irrigation increases yields by 50%, while fertilization does so by more than 25% [33]. The greatest yield, i.e., 15.12 Mg ha −1 , was obtained for object W(+)/N80, and the difference between objects W(−)/N80 and W(+)/N80 was only 7.6%, testifying to the minor impact of irrigation on the dry weight yield at this fertilization dose.…”
Section: The Mass and Energy Balance During Cup Plant Biomass Gasificmentioning
confidence: 96%